A comparative study on the exterior and interior design features of middle class houses in the first district of Laguna - Realingo, Christine S.; Mayo, Adelaida Villaraza (2006.)
The first district of Laguna is one of the fast-developing areas nowadays in terms of urbanization, economic activity, and population and is also very accessible from Metro Manila. These, plus the more affordable residential lots in the area, many people, mostly from the middle class, started to reside in the said area. With the increasing demands for housing, people have started to build and renovate houses for comfort and better living conditions. With numerous constructions taking place, noticeable similarities could be observed on newly-built or recently renovated houses and this observation became the focus of this study. Using a number of six residences from three towns that comprise the First District of Laguna as samples, this comparative study identified, described, and analyzed the similarities among middle class single detached dwellings in the first district of Laguna. Furthermore, this study tried to look into the factors that may have caused such similarities in these houses. This study used a multi-method research design that was mainly based on field research. Questionnaires and interviews, site visitations, and taking of photographs were the instrumentations used in gathering data. Gathered data were classified and organized through content analysis to deduce significant patterns that were conveyed by the information gathered. The Elements and Principles of Design, the study of Urban Semiotics, and the study of Symbolic Interaction were used to decipher cultural meanings behind the physical similarities of the houses. Data showed that there were similarities in the exterior of the houses as seen in their color schemes, areas in the exterior space, and design features such as their window types, mouldings and trimmings. Similarities in the interior, on the other hand, were evident in the color scheme, ceiling design, finishing materials, and furniture pieces. Through interviews with the respondents, it was found out that the similarities were influenced by the socio-economic status, exposure to interior design, and foreign influences brought about by members of the family working abroad.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Architecture, Domestic -- Philippines -- Laguna; Interior architecture -- Philippines -- Laguna